2003
DOI: 10.1177/0095798403256965
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Stress and Coping Resources Interact to Predict Blood Pressure Reactivity in Black College Students

Abstract: This study examined the effects of subjective stress and coping resources on blood pressure reactivity. Sixty-nine Black college students (mean age = 23.58 years) completed the Life Experiences and Stress Scale to explore the subjective stressfulness associated with life events, the Coping Orientations to Problems Experienced Scale to measure usual ways of coping, and a standardized serial addition laboratory challenge during which blood pressure was assessed. Multiple regression analyses revealed that the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
0
9
1
Order By: Relevance
“…Additionally, although active coping (i.e., trying to change something about the encounter) is generally seen as more health protective than passive coping (i.e., managing/minimizing the distress associated with the experience such as with emotion suppression), studies suggest that chronic deployment of active coping strategies may be health damaging, especially when the stressor is perceived as particularly stressful and/or uncontrollable . AA women have reported racial discrimination as a particularly salient form of psychosocial stress and note that “racism is going to be there, no matter what you do it's going to be there.” Hence, in such cases, where racial discrimination is perceived as chronic and uncontrollable, the benefits of active coping may be weakened .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although active coping (i.e., trying to change something about the encounter) is generally seen as more health protective than passive coping (i.e., managing/minimizing the distress associated with the experience such as with emotion suppression), studies suggest that chronic deployment of active coping strategies may be health damaging, especially when the stressor is perceived as particularly stressful and/or uncontrollable . AA women have reported racial discrimination as a particularly salient form of psychosocial stress and note that “racism is going to be there, no matter what you do it's going to be there.” Hence, in such cases, where racial discrimination is perceived as chronic and uncontrollable, the benefits of active coping may be weakened .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, research has shown that people who adopt problem-and/or emotion-focused coping strategies (e.g. positive reinterpretation) under conditions of high stress respond with less exaggerated systolic and diastolic blood pressure changes (Clark, 2003;Nyklíček & Vingerhoets, 2009). After being presented with instructions informing participants that they would be giving two speeches in an unfamiliar surrounding while connected to an ECG monitor, impedance cardiography equipment, and a blood pressure cuff, it is likely that cardiovascular stress responses were activated prior to testing.…”
Section: Discussionmentioning
confidence: 99%
“…The second approach, which is used in the present study, is similar to the previous one except researchers have used general (Carver, Scheier, & Weintraub, 1989;James, Harnett, & Kalsbeek, 1983) and situation-specific (Lazarus & Folkman, 1984) coping responses that are purported to be more universal (i.e., nonethnicity specific). Studies elucidating the range of general and situation-specific coping responses in Blacks are warranted, given research indicating that (a) these responses are associated with vascular reactivity (Clark & Anderson, 2001), resting blood pressure (Clark & Harrell, 1982;Krieger & Sidney, 1996), psychological well-being or self-rated health (Williams et al, 1997), and racism-related stress (Utsey, Ponterotto, Reynolds, & Cancelli, 2000b); and (b) these responses interact with family history of hypertension (Clark, 2003a), subjective stress (Clark, 2003c), and perceived intergroup racism (Clark, 2003b;Clark & Adams, in press) to predict blood pressure reactivity and psychological well-being (Bowen-Reid & Harrell, 2002). Findings from this line of research have the longer term potential of better informing prevention and intervention strategies aimed at reducing the untoward psychological and physiological effects of perceived racism.…”
Section: Coping With Perceived Racismmentioning
confidence: 99%